GREEN HUMAN RESOURCES MANAGEMENT AS A DETERMINANT OF ENVIRONMENTAL PERFORMANCE AND COMPANY PERFORMANCE - Ashabul Yamin (Management Studies and Business Journal (PRODUCTIVITY), 2026)
The escalation of global sustainability issues compels organizations to transform the human resource function into a driver of green strategy. This study aims to analyze the role of Green Human Resource Management (GHRM) as a determinant of environmental performance and firm performance. Using a systematic narrative review of internationally reputable literature (Scopus), this study synthesizes findings based on the Ability Motivation Opportunity (AMO) framework and the Resource-Based View (RBV). The results indicate that the bundle of GHRM practices encompassing green recruitment, training, and performance management significantly enhances employees’ pro environmental behavior and operational efficiency. These mechanisms are strengthened by green organizational culture and ethical leadership as moderating variables. Although the relationship between GHRM and financial performance is indirect and often mediated by green innovation, these practices are shown to build long-term competitive advantage through enhanced organizational reputation and legitimacy. In conclusion, integrating environmental values into HR systems is critical for developing a sustainable business ecosystem. Practical implications for managers include the need to design reward systems aligned with environmental performance.